Recurrent common bile duct lithiasis - Praderi, Raúl (2021)
A case of recurrent lithiasis in the common duct which is a more frequent disease than is generally supposed is presented. The interest of the case lies in the fact that the patient had been operated three years before by the same surgeon, antd the biliary tract had been left clean as can be seen in the cholangiography.